An integrated surveillance system using RFID and vision-tracking technologies. (18th November 2009) - Chang, I-Cheng; Yang, Jia-Hong; Chang, Teng-Hsun; Kao, Yu-Kai
This paper proposes a new surveillance system that combines the advantages of vision and RFID technologies. The system consists of two major parts: 1 a tracking system that finds the target's position using RFID and vision methods, and then applies static and active cameras to obtain global information and local detailed features of the target; 2 a decision system that first recognises and records the events and then sends orders to other functions to commence further processing. A central data management is employed to allocate resources and assign target priority for the decision system. The experimental results demonstrated that the proposed approach can work effectively for tracking the activities of invaders.